Rational Design and Biological Application of Antioxidant Nanozymes - Tian, Ruizhen; Xu, Jiayun; Luo, Quan; Hou, Chunxi; Liu, Junqiu (Frontiers in Chemistry, 2021)
Nanozyme is a type of nanostructured material with intrinsic enzyme mimicking activity, which has been increasingly studied in the biological field. Compared with natural enzymes, nanozymes have many advantages, such as higher stability, higher design flexibility, and more economical production costs. Nanozymes can be used to mimic natural antioxidant enzymes to treat diseases caused by oxidative stress through reasonable design and modification. Oxidative stress is caused by imbalances in the production and elimination of reactive oxygen species (ROS) and reactive nitrogen species (RNS). This continuous oxidative stress can cause damage to some biomolecules and significant destruction to cell structure and function, leading to many physiological diseases. In this paper, the methods to improve the antioxidant properties of nanozymes were reviewed, and the applications of nanozyme antioxidant in the fields of anti-aging, cell protection, anti-inflammation, wound repair, cancer, traumatic brain injury and nervous system diseases were introduced. Finally, the future challenges and prospects of nanozyme as an ideal antioxidant were discussed.